Breast cancer screening in women at high risk of hereditary breast cancer: an Australian experience. Issue 4 (30th September 2020) - Bennett, Ian; Tourani, Saam; Cockburn, Linda; Reasbeck, Jane; Grobbelaar, Neels; Dann, Sonia; Patrikios, Penny; Brazier, Jane
Abstract: Background: While population‐based breast screening is a well‐documented health strategy worldwide, very few centres offer breast‐screening programmes specifically targeted at women at high risk of hereditary breast cancer. We present our experience with multimodality breast screening in a high‐risk population. Methods: The outcomes from a familial breast cancer clinic at the North Brisbane BreastScreen Queensland Service providing a multimodality screening programme for high‐risk women were reviewed from the prospectively maintained database between 2011 and 2018. Results: Over the 8 years of study period, a total of 6686 annual screening rounds were performed for 823 asymptomatic women at high risk of hereditary breast cancer. As a result, 40 cancers were diagnosed including 25 invasive ductal cancers, three invasive lobular cancers, two invasive cancers with mixed ductal and lobular features and 10 ductal carcinomas in situ . Ultrasound and mammography detected 72.5% (29/40) and 55% (22/40) of the cancers, respectively. A total of 3672 magnetic resonance imaging studies were performed. Ten (25%) cancers were initially only seen on magnetic resonance imaging including seven invasive ductal cancers, one invasive lobular cancer and two high‐grade ductal carcinomas in situ . The cancer detection rate for first‐round screening was 13.3 cancers per 1000 women screened, with 4.9 cancers per 1000 women detected on subsequent‐round screening. One interval cancer occurred in the study period. Conclusion: Multimodality breast screening of younger women at high risk of hereditary breast cancer is effective with the yield substantially exceeding the results from established breast screening programmes in older women. Co‐location of this service within BreastScreen Australia efficiently shares resources. Abstract : Multimodality screening of younger women at high risk of hereditary breast cancer is effective, and the yield substantially exceeds the results from established breast screening programmes in older women. Magnetic resonance imaging offers incremental efficiency in detecting cancers in this high‐risk population and is a useful addition to the screening armamentarium. Co‐location of the high‐risk screening service within BreastScreen Australia offered efficient use of resources and skilled personnel.